How to factor an algebraic expression stepbystep?
Method to factoring algebraic expression by grouping:
(i) From the groups of the given expression a factor can be taken out from each group.
(ii) Factorize each group
(iii) Now take out the factor common to group formed.
Now we will learn how to factor the terms by grouping.
Solved examples of factoring terms by grouping:
1. Factoring of algebraic expression:
(i) 2ax + ay + 2bx + by
Solution:
2ax + ay + 2bx + by
= a(2x + y) + b(2x + y)
= (2x + y) (a + b)
(ii) 3ax  bx  3ay + by
Solution:
3ax  bx  3ay + by
= x(3x  b)  y(3x  b)
= (3x  b) (x  y)
(v) am  an + bm – bn
Solution:
am  an + bm  bn
= a(m  n) + b(m  n)
= (m  n) (a + b)
`2. Factorize the following algebraic expression:
(i) 6x + 3xy + y + 2
Solution:
6x + 3xy + y + 2
= (6x + 3xy) + (y + 2)
= 3x(2 + y) + 1(2 + y)
= 3x(y + 2) + 1(y + 2)
= (y + 2) (3x + 1)
= (3x + 1) (y + 2)
(ii) 3x^{3} + 5x^{2} + 3x + 5= (x  1) [1  (x  1) + a]
= (x  1) [1  x + 1 + a]
= (x  1) (2 + a  x)
`8th Grade Math Practice
From Factoring Terms by Grouping to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.